2019
DOI: 10.1111/nph.16043
|View full text |Cite
|
Sign up to set email alerts
|

Conifers depend on established roots during drought: results from a coupled model of carbon allocation and hydraulics

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 96 publications
1
76
0
Order By: Relevance
“…It has also been suggested that changes in carbon allocation patterns due to the drought could stimulate root growth into deeper soil layers. Mackay et al [31] tested this hypothesis for conifer trees using a new modelling framework, and they concluded that the trees shifted water uptake among existing roots rather than growing new roots. Oishi et al [32], who studied water relations of an oak-hickory forest in North Caroline, USA, for several years including 1 year with severe drought, also found that the canopy transpiration was not reduced by drought for the same reason For reasons discussed above, it was not entirely unexpected that the Gs anomaly did not explain the anomaly in evaporation, E_diff (figure 8).…”
Section: Discussion (A) Drought and Evaporationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that changes in carbon allocation patterns due to the drought could stimulate root growth into deeper soil layers. Mackay et al [31] tested this hypothesis for conifer trees using a new modelling framework, and they concluded that the trees shifted water uptake among existing roots rather than growing new roots. Oishi et al [32], who studied water relations of an oak-hickory forest in North Caroline, USA, for several years including 1 year with severe drought, also found that the canopy transpiration was not reduced by drought for the same reason For reasons discussed above, it was not entirely unexpected that the Gs anomaly did not explain the anomaly in evaporation, E_diff (figure 8).…”
Section: Discussion (A) Drought and Evaporationmentioning
confidence: 99%
“…Mackay et al . [ 31 ] tested this hypothesis for conifer trees using a new modelling framework, and they concluded that the trees shifted water uptake among existing roots rather than growing new roots. Oishi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Though our analysis formally acknowledges uncertainty in parameter estimation (Figures , , , and ), our results and the following discussion are predicated on the structure of EcH 2 O‐iso and our representations of tree water storage as adequate abstractions of relevant ecohydrological processes. Future research should more critically evaluate RWU and mixing with more frequent measurements of δ XYLEM through time and explore the possibility of time‐varying ecohydrologic parameterizations or more physically based representations of RWU demand that adequately describe temporal variations in RWU (e.g., Mackay et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although EcH 2 O‐iso accounts for variability in RWU depth as water availability fluctuates within soil layers, the model incorporates the assumption that RWU depth demand profiles, as defined by the K ROOT parameter, are time invariant throughout each simulation. Knighton et al (Knighton, Coneelly, & Walter, ; Knighton, Souter‐Kline, et al, ) and Mackay et al () provided evidence that some coniferous trees shift RWU demand to deeper layers through periods of shallow soil water deficit. Recent studies have supported seasonal variations in RWU demand plasticity across a variety of tree species highlighting compensation mechanisms between wetter and water‐limited layers (e.g., De Jong van Lier, Van Dam, Metselaar, De Jong, & Duijnisveld, ; Javaux, Schröder, Vanderborght, & Vereecken, ; Nehemy et al, ; Brinkmann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research considering the myriad of processes that can promote mortality is the most likely to yield mechanistic insight from which simplified modeling schemes can be developed. Second, understanding the degree of hydraulic failure belowground has emerged as a critical frontier, as model analysis suggests hydraulic failure in the roots and/or root–soil interface may dominate during drought (McDowell et al ., ; D. M. Johnson et al ., ; Mackay et al ., ). This is a large challenge due to the difficult nature of quantifying plant hydraulics belowground.…”
Section: Advance: Understanding and Simulation Of Hydraulic Failure Amentioning
confidence: 97%